2010
DOI: 10.1103/physrevb.82.024413
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic strong coupling in a spin-photon system and transition to classical regime

Abstract: We study the energy level structure of the Tavis-Cumming model applied to an ensemble of independent magnetic spins s =1/ 2 coupled to a variable number of photons. Rabi splittings are calculated and their distribution is analyzed as a function of photon number n max and spin system size N. A sharp transition in the distribution of the Rabi frequency is found at n max Ϸ N. The width of the Rabi frequency spectrum diverges as ͱ N at this point. For increased number of photons n max Ͼ N, the Rabi frequencies con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
104
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 27 publications
8
104
1
Order By: Relevance
“…At the same time, the quasi-harmonic nature of the system can lead to interesting effects, where the two-or multi-level nature of a system can be interchanged and tuned 2 . Spin systems benefit from relatively large coherence and relaxation times, which makes them suitable as quantum bit implementations or as a new type of quantum random access memory 6,10,18,27 . In some studies, spin qubits operation is demonstrated at temperatures up to ambient 1 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the quasi-harmonic nature of the system can lead to interesting effects, where the two-or multi-level nature of a system can be interchanged and tuned 2 . Spin systems benefit from relatively large coherence and relaxation times, which makes them suitable as quantum bit implementations or as a new type of quantum random access memory 6,10,18,27 . In some studies, spin qubits operation is demonstrated at temperatures up to ambient 1 .…”
Section: Introductionmentioning
confidence: 99%
“…SEs of organic radicals can thus combine narrow magnetic transitions and high spin densities. For this reason, they are particularly suitable for reaching the strong coupling regime in a microwave cavity [18][19][20], while their versatility inspires the implementation of quantum gates [21].Here we exploit these features in order to demonstrate the coherent coupling between distinguishable SEs. By using (3,5-dichloro-4-pyridyl)bis(2,4,6-trichlorophenyl)methyl radicals (PyBTM) [22], we first show that the strong-coupling regime is largely achieved in a broad temperature range, with values of the cooperativity reaching 4300 at 2 K. This allows us to provide an experimental evidence of the coherent coupling between up to three spatially separated SEs, mediated by the cavity mode of a high T c YBCO/sapphire coplanar resonator.…”
mentioning
confidence: 99%
“…Multi-level systems are promising for implementing few-qubits algorithms 12 or as quantum memories [13][14][15][16] . For quantum technology applications, a higher sensitivity electron spin resonance (ESR) measurement is needed to be able to manipulate spins in mesoscopic crystals placed on superconducting chips [17][18][19][20][21] .…”
mentioning
confidence: 99%